Serum Th‐2 cytokines and FEV1 decline in WTC‐exposed firefighters: A 19‐year longitudinal study. Issue 10 (20th July 2021) - Weiden, Michael D.; Singh, Ankura; Goldfarb, David G.; Putman, Barbara; Zeig‐Owens, Rachel; Schwartz, Theresa; Cohen, Hillel W.; Prezant, David J.
Abstract: Background: Accelerated‐FEV1 ‐decline, defined as rate of decline in FEV1 > 64 ml/year, is a risk factor for asthma and chronic obstructive pulmonary disease in World Trade Center (WTC)‐exposed firefighters. Accelerated‐FEV1 ‐decline in this cohort is associated with elevated blood eosinophil concentrations, a mediator of Th‐2 response. We hypothesized that an association exists between Th‐2 biomarkers and FEV1 decline rate in those with accelerated‐FEV1 ‐decline. Methods: Serum was drawn from Fire Department of the City of New York (FDNY) firefighters 1–6 months (early) ( N = 816) and 12–13 years (late) ( N = 983) after 9/11/2001. Th‐2 biomarkers IL‐4, IL‐13, and IL‐5 were assayed by multiplex Luminex. Individual FEV1 decline rates were calculated using spirometric measurements taken: (1) between 9/11/2001 and 9/10/2020 for the early biomarker group and (2) between late measurement date and 9/10/2020 for the late biomarker group. Associations of early and late Th‐2 biomarkers with subsequent FEV1 decline rates were analyzed using multivariable linear regression controlling for demographics, smoking status, and other potential confounders. Results: In WTC‐exposed firefighters with accelerated‐FEV1 ‐decline, IL‐4, IL‐13, and IL‐5 measured 1–6 months post‐9/11/2001 were associated with greater FEV1 decline ml/year between 9/11/2001 and 9/10/2020 (−2.9 ± 1.4 ml/year per IL‐4 doubling; −8.4 ± 1.2 ml/year per IL‐13 doubling; −7.9 ± 1.3 ml/year per IL‐5 doubling). Among late measured Th‐2 biomarkers, only IL‐4 was associated with subsequent FEV1 decline rate (−4.0 ± 1.6 ml/year per IL‐4 doubling). Conclusions: In WTC‐exposed firefighters with accelerated‐FEV1 ‐decline, elevated serum IL‐4 measured both 1–6 months and 12–13 years after 9/11 is associated with greater FEV1 decline/year. Drugs targeting the IL‐4 pathway may improve lung function in this high‐risk subgroup.